Analysis on the Mechanical Characteristics and Energy Conversion of Sandstone Constituents under Natural and Saturated States - Xinrong Liu; Jun Liu (Advances in Materials Science and Engineering)
Given that apparent differences exist between physical and mechanical properties of sandstone constituents under natural and saturated states, uniaxial and triaxial tests of sandstone specimens taken from a deep tunnel in Chongqing under the two states were, respectively, conducted in the laboratory. Analysis on the energy conversion of sandstone constituents under natural and saturated states reveals the varying strain energy conversion mechanisms under the two different conditions. It shows that water saturation has significant effects on the strength and deformation characteristics of sandstone constituents. The load bearing capacity and nondeformability decrease once the sandstone constituents are saturated. The strength weakening due to water in saturated specimens mainly takes place after the dilatancy stress σcd and reaches its maximum at the peak stress σf. Strain energies of sandstone constituents under the saturated state are lower than those under the natural state, which indicates that water reduces the strain energy absorption. The strain energy of specimens at the peak stress point under the two states has a good linear positive correlation with the confining pressure. Moreover, the fitting curve of the case under the natural state has a higher slope, which means that the strain energy under such state is more sensitive to the confining pressure than that under the saturated state.